Risk Assessment and Mitigation Strategy in The Halal Broiler Supply Chain - Titania Miranda Sari; Dini W (Jurnal Riset Ilmu Teknik, 2023)
Indonesia's chicken meat supply chain usually starts from large-scale chicken farmers, distributed to medium-scale chicken agents/toke, traditional slaughter chicken traders, then restaurants and homemakers as end customers. In such a long supply chain, contamination may cause the halal status of slaughtered chicken products to be questioned. The problem studied is the potential risk that can cause contamination of halal slaughtered chicken products from suppliers to end customers. Therefore, this study aims to identify the risk of contamination in the halal supply chain of slaughtered chicken products and obtain recommendations for corrective actions so that slaughtered chicken products are maintained halal. Data is processed using manual Interpretive Structural Modeling (ISM) methods, ISM Professional V 5.0 software, MICMAC Analysis, and Failure Mode and Effect Analysis (FMEA). The conclusions obtained from this study are the identification of the risk of contamination of the halal supply chain in slaughtered chicken products consisting of 26 risk elements, recommendations for corrective actions based on the assessment of contextual relationships between risk elements, among others, slaughterers should be given adequate rest time and the number of workers should be adjusted to the workload, and recommendations for corrective actions based on the assessment of the risk level of each element, among others, preferably  slaughterers are given education and motivation; Every slaughterer should be required to attend halal slaughterer training; The slaughterer should be motivated to always apply the slaughter training he participates in; ante-mortem should be done before the chickens are delivered; it is best to provide enough containers for chickens after slaughter; And the chicken should be left for up to 3 minutes after slaughter and make sure the chicken has completely died.